Multiple Modular Engineering of Bacillus Amyloliquefaciens Cell Factories for Enhanced Production of Alkaline Proteases From B. Clausii - Zhang, Jinfang; Zhu, Baoyue; Li, Xinyue; Xu, Xiaojian; Li, Dengke; Zeng, Fang; Zhou, Cuixia; Liu, Yihan; Li, Yu; Lu, Fuping (Frontiers in Bioengineering and Biotechnology, 2022)
Bacillus amyloliquefaciens is a generally recognized as safe (GRAS) microorganism that presents great potential for the production of heterologous proteins. In this study, we performed genomic and comparative transcriptome to investigate the critical modular in B. amyloliquefaciens on the production of heterologous alkaline proteases (AprE). After investigation, it was concluded that the key modules affecting the production of alkaline protease were the sporulation germination module (Module I), extracellular protease synthesis module (Module II), and extracellular polysaccharide synthesis module (Module III) in B. amyloliquefaciens. In Module I, AprE yield for mutant BA ΔsigF was 25.3% greater than that of BA Δupp. Combining Module I synergistically with mutation of extracellular proteases in Module II significantly increased AprE production by 36.1% compared with production by BA Δupp. In Module III, the mutation of genes controlling extracellular polysaccharides reduced the viscosity and the accumulation of sediment, and increased the rate of dissolved oxygen in fermentation. Moreover, AprE production was 39.6% higher than in BA Δupp when Modules I, II and III were engineered in combination. This study provides modular engineering strategies for the modification of B. amyloliquefaciens for the production of alkaline proteases.